Pathological complete response in esophageal squamous cell carcinoma complicated by malignant fistula via neoadjuvant immunotherapy, chemoradiotherapy, and nutritional support: a case report - Li, Nanxi; Lan, Mei; Yao, Wenxiu; Zhu, Yixiang; Wang, Qifeng (Frontiers in Immunology, 2026)
Esophageal cancer presents a formidable global health challenge, particularly when complicated by esophageal fistulas, which historically confer a dismal prognosis and severely limit therapeutic options. We report a challenging case of locally advanced esophageal squamous cell carcinoma (ESCC) complicated by an esophageal fistula that ultimately achieved a pathological complete response (pCR). The patient, a male in his 50s, presented with cough and dysphagia and was diagnosed with Stage IVA ESCC. Notably, an esophageal fistula was identified at the initial presentation, posing a threat to treatment. Aggressive enteral nutritional support via nasogastric tube placement and subsequent percutaneous endoscopic gastrostomy (PEG) was promptly initiated. This allowed the patient to successfully complete neoadjuvant therapy consisting of the anti-PD-1 antibody tislelizumab, paclitaxel, carboplatin, and concurrent intensity-modulated radiation therapy (IMRT). Following this multimodal regimen, the patient was reassessed as resectable following response to therapy status. Subsequent radical esophagectomy revealed no residual tumor cells in the primary lesion or dissected lymph nodes (ypT0N0M0), confirming pCR. Immunohistochemical analysis of pre-treatment biopsies demonstrated PD-L1 positivity and high infiltration of CD8+ T cells, suggesting that a robust immune-active microenvironment favored the efficacy of PD-1 blockade. This case underscores the feasibility of integrating immunotherapy with chemoradiotherapy in ESCC patients complicated by esophageal fistulas when supported by rigorous nutritional management.